Freestyle Snowsport - Noonan, J. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Working with elite freestyle athletes presents strength and conditioning coaches and perfor. mance practitioners with a range of challenges which have been outlined in this chapter. The most noteworthy challenges affecting athletes appear to exist in travel fatigue, training in the cold, physical training fatigue, a frequently changing training `base`, and disturbed sleep and nutritional behaviours. Due to the fact that freestyle snowsport is a relatively new discipline, programme resources and the number of performance staff working with each team has steadily risen in the past decade. Most teams now have access to a fulltime strength and conditioning coach/athletic trainer, in addition to a once seldom recruited physiotherapist. Furthermore, there has been an explosion in interest of microtechnology within the sport, where numerous devices are being developed to measure biomechanical and physical demands of the sport. Until further literary evidence regarding the physical profile of athletes becomes available, strength and conditioning coaches and sport scientists should make every effort to connect with technical coaches and medical staff to increase understanding and to identify performance threats and issues facing this population. It is hoped that this chapter will provide strength and conditioning coaches and practitioners alike with insights and knowledge pertaining to the modern physical needs of freestyle snowspott athletes. It should be stressed that the importance of establishing a set of simple, performance based questions developed from an understanding of traditional sports in order to inform reasoning and guide practice should not be overlooked, alongside developing a series of ecological solutions to performance problemis based on observations, with creativity and simplicity held firmly at the centre of our thought process. Within this chapter, recommendations from alternative sports, alongside the author's experience within the field, have been used to address gaps in the literature and direct the reader to a clearer understanding of the current challenges, knowledge and training opportunities for the practitioner within freestyle snowsport.